Parole Board Members’ Views of Sex Offender Registration and Community Notification - Tewksbury, Richard (American journal of criminal justice, 2012)
Little is known about how criminal justice officials perceive fairness, efficacy or scope of sex offender registration and community notification procedures, despite their importance in implementing such policies. There is also scant literature regarding parole board members and their attitudes or approaches to their work. This study addresses both issues by examining the attitudes and beliefs regarding sex offender registration and community notification among members of state parole boards. Using a survey methodology, including the Community Attitudes Toward Sex Offenders (CATSO) scale (Church, Wakeman, Miller, Clements, & Sun, 2008 ), parole board members are shown to hold moderate views of the importance of such practices and to frequently question the efficacy and scope of registration and community notification. Additionally, the CATSO is shown to not be of assistance for understanding the views of parole board members.